The Nehari Manifold for a Class of Singular $ψ$-Riemann-Liouville Fractional with $p$-Laplacian Operator Differential Equations (Advances in Applied Mathematics and Mechanics, 2024)
Using Nehari manifold method combined with fibring maps, we show theexistence of nontrivial, weak, positive solutions of the nonlinear $ψ$-Riemann-Liouvillefractional boundary value problem involving the $p$-Laplacian operator, given by where $λ>0, 0